2021
DOI: 10.1007/s10961-021-09860-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of research as source and signal: revisiting the valorization process beyond substitution vs complementarity

Abstract: In recent years, the growing interest of universities in valorization of research activities (tipically through technology transfer—patenting and licensing—and academic entrepreneurship) has generated a debate on its impact on scientific knowledge production. There have been controversies on the potentially negative effect of university research valorization on public research, in terms of quality, long term vs short term orientation, and accessibility. The debate has been traditionally framed in terms of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 121 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Blume-Kohout et al (2009) provided similar evidence of complementarity by examining federal and nonfederal funding in life sciences for U.S. universities, while Muscio et al (2013) found that government funding to Italian universities complements funding received from private actors in terms of research contracts and consulting activities. This suggests that external sponsors can interpret internal/public funding as a signal of research quality, an argument that is also supported by recent evidence from Bonaccorsi et al (2021) on the positive relationship between research quality and its valorization (i.e., patents and spin-off companies) in the case of the Italian Evaluation of Research Quality VQR (2011)(2012)(2013)(2014).…”
Section: Research Funding: Complementarity and Substitutabilitymentioning
confidence: 64%
“…Blume-Kohout et al (2009) provided similar evidence of complementarity by examining federal and nonfederal funding in life sciences for U.S. universities, while Muscio et al (2013) found that government funding to Italian universities complements funding received from private actors in terms of research contracts and consulting activities. This suggests that external sponsors can interpret internal/public funding as a signal of research quality, an argument that is also supported by recent evidence from Bonaccorsi et al (2021) on the positive relationship between research quality and its valorization (i.e., patents and spin-off companies) in the case of the Italian Evaluation of Research Quality VQR (2011)(2012)(2013)(2014).…”
Section: Research Funding: Complementarity and Substitutabilitymentioning
confidence: 64%
“…According to Fini et al (2017) non-state universities have greater institutional autonomy and are less constrained in their technology transfer activities. Others have found that state universities have greater success when it comes to commercially viable outputs (Bonaccorsi et al, 2021) because private universities may be more teaching-oriented with less emphasis on either research or TM activities (de la Torre et al, 2017). Previous research has shown that universities of applied sciences are more engaged in regional knowledge transfer than regular universities (Jaeger and Kopper, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous research has shown that universities of applied sciences are more engaged in regional knowledge transfer than regular universities (Jaeger and Kopper, 2014). Additionally, universities can be distinguished into generalist and specialist universities where generalist universities have better conditions for commercialisation due to higher internal collaboration between different scientific disciplines, such as interaction between STEM and social sciences and humanities (SSH) (Bonaccorsi et al, 2021; Giuri et al, 2019). As for location, knowledge transfer is more likely when industry and universities are in close geographic proximity (Wang et al, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%